Thioesterase superfamily member 1 suppresses cold thermogenesis by limiting the oxidation of lipid droplet-derived fatty acids in brown adipose tissue - Okada, Kosuke (Mol Metab, 2016)
OBJECTIVE: Non-shivering thermogenesis in brown adipose tissue (BAT) plays a central role in energy homeostasis. Thioesterase superfamily member 1 (Them1), a BAT-enriched long chain fatty acyl-CoA thioesterase, is upregulated by cold and downregulated by warm ambient temperatures. Them1(−/−) mice exhibit increased energy expenditure and resistance to diet-induced obesity and diabetes, but the mechanistic contribution of Them1 to the regulation of cold thermogenesis remains unknown. METHODS: Them1(−/−) and Them1(+/+) mice were subjected to continuous metabolic monitoring to quantify the effects of ambient temperatures ranging from thermoneutrality (30 °C) to cold (4 °C) on energy expenditure, core body temperature, physical activity and food intake. The effects of Them1 expression on O(2) consumption rates, thermogenic gene expression and lipolytic protein activation were determined ex vivo in BAT and in primary brown adipocytes. RESULTS: Them1 suppressed thermogenesis in mice even in the setting of ongoing cold exposure. Without affecting thermogenic gene transcription, Them1 reduced O(2) consumption rates in both isolated BAT and primary brown adipocytes. This was attributable to decreased mitochondrial oxidation of endogenous but not exogenous fatty acids. CONCLUSIONS: These results show that Them1 may act as a break on uncontrolled heat production and limit the extent of energy expenditure. Pharmacologic inhibition of Them1 could provide a targeted strategy for the management of metabolic disorders via activation of brown fat.